2021
DOI: 10.1212/wnl.0000000000012602
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Silent Cerebrovascular Disease Identified Using Natural Language Processing and Future Ischemic Stroke

Abstract: Background and Objective:Silent cerebrovascular disease (SCD), comprised of silent brain infarction (SBI) and white matter disease (WMD), is commonly found incidentally on neuroimaging scans obtained in routine clinical care. However, their prognostic significance is not known. We aimed to estimate the incidence of, and risk increase in, future stroke in patients with incidentally-discovered SCD.Methods:Patients in Kaiser Permanente Southern California (KPSC) health system aged ≥ 50, without prior ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…A prior study in this cohort found that CBI was a “stroke equivalent” in terms of the risk of future clinically evident stroke. 27 While the findings here are similar to some studies in screened cohorts, 3,28 there are additional insights not previously known. In particular, we found a dramatic increase in the incidence of dementia following CT-detected CCD compared to MRI-detected CCD.…”
Section: Discussionsupporting
confidence: 88%
“…A prior study in this cohort found that CBI was a “stroke equivalent” in terms of the risk of future clinically evident stroke. 27 While the findings here are similar to some studies in screened cohorts, 3,28 there are additional insights not previously known. In particular, we found a dramatic increase in the incidence of dementia following CT-detected CCD compared to MRI-detected CCD.…”
Section: Discussionsupporting
confidence: 88%
“…In previous work, we developed and validated natural language processing (NLP) algorithms to identify the presence of id‐CCD and severity of incidentally discovered WMD (id‐WMD) using neuroimaging reports and deployed these algorithms in a large integrated health system, 13 thereby permitting us to examine associations between exposures and rare outcomes in a cohort by using “big data.” We previously found that id‐CCD is strongly predictive of subsequent stroke 5 and dementia, 14 particularly in younger patients and in those with more severe WMD. In this study, we examined the association of id‐CBI and id‐WMD with a subsequent diagnosis of PD, using NLP of routinely obtained neuroimaging reports to identify these lesions.…”
Section: Introductionmentioning
confidence: 96%
“…In previous work, we developed and validated natural language processing (NLP) algorithms to identify the presence of CCD and severity of WMD using neuroimaging reports and deployed these algorithms in a large integrated health system, 13 thereby permitting us to examine associations between exposures and rare outcomes in a cohort by using 'big data'. We previously found that CCD is strongly predictive of subsequent stroke 14 and dementia, 15 particularly in younger patients and in those with more severe WMD. In this study, we examined the association of CBI and WMD with a subsequent diagnosis of PD, using NLP of routinely obtained neuroimaging reports to identify these lesions.…”
Section: Introductionmentioning
confidence: 93%